2013
DOI: 10.1055/s-0033-1344027
|View full text |Cite
|
Sign up to set email alerts
|

Japanese multicenter experience of endoscopic necrosectomy for infected walled-off pancreatic necrosis: The JENIPaN study

Abstract: Endoscopic necrosectomy can be an effective technique for infected WOPN and requires a relatively short treatment period. However, serious complications can arise, including death. Therefore, patients should be carefully selected, and knowledgeable, skilled, and experienced operators should perform the procedure. Further research into safer technologies is required in order to reduce the associated morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 14 publications
3
113
0
2
Order By: Relevance
“…Similar outcomes have been observed in subsequent studies [47,48], and a recent meta-analysis found pooled rates of treatment success, complications and mortality of 81%, 35% and 6%, respectively [49]. Reported complications include perforation, air embolism, and bleeding, which occurs in 3%–21% of patients [46,47,50]. Therefore, despite the fact that DEN may contribute to accelerated patient recovery and clinical resolution of infected WON, the morbidity and mortality associated with the procedure should limit its use to circumstances in which patients have failed to improve after appropriate transluminal drainage, with a target treatment endpoint of clinical resolution of significant symptoms, not radiological resolution.…”
Section: Direct Endoscopic Necrosectomysupporting
confidence: 92%
See 1 more Smart Citation
“…Similar outcomes have been observed in subsequent studies [47,48], and a recent meta-analysis found pooled rates of treatment success, complications and mortality of 81%, 35% and 6%, respectively [49]. Reported complications include perforation, air embolism, and bleeding, which occurs in 3%–21% of patients [46,47,50]. Therefore, despite the fact that DEN may contribute to accelerated patient recovery and clinical resolution of infected WON, the morbidity and mortality associated with the procedure should limit its use to circumstances in which patients have failed to improve after appropriate transluminal drainage, with a target treatment endpoint of clinical resolution of significant symptoms, not radiological resolution.…”
Section: Direct Endoscopic Necrosectomysupporting
confidence: 92%
“…Despite these encouraging results, complications were common, occurring in 26% of patients, with 7.5% mortality. Similar outcomes have been observed in subsequent studies [47,48], and a recent meta-analysis found pooled rates of treatment success, complications and mortality of 81%, 35% and 6%, respectively [49]. Reported complications include perforation, air embolism, and bleeding, which occurs in 3%–21% of patients [46,47,50].…”
Section: Direct Endoscopic Necrosectomysupporting
confidence: 77%
“…15,16 In addition to these therapies, endoscopic necrosectomy for infected, walled-off pancreatic necrosis has been developed, which enables effective intervention with morbidity and mortality lower than does surgical necrosectomy. 17,18 The contribution of this less invasive intervention to the improved prognosis of patients with AP also needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In the present era, endoscopic necrosectomy is preferred over open or minimally invasive surgical necrosectomy. A number of studies have established the safety and efficacy of DEN[60-62]. Endoscopic necrosectomy is associated with reduced formation of pancreatic fistula as compared to surgical drainage[10].…”
Section: Direct Endoscopic Necrosectomymentioning
confidence: 99%